THE EFFECTS OF EDUCATIONAL CARD GAME ON STUDENTS' CREATIVITY AND CONCEPTUAL UNDERSTANDING IN LEARNING EXCRETORY SYSTEM - Azizah, Nisa Nur (2015)
This research investigated the effect of educational card game ON students' creativity and conceptual understanding in learning excretory system. The method which is used in this research was quasi experiment with non-equivalent-groups pretest-posttest design. Data are collected from two biology classes, namely experiment class (N=13) and control class (N=18) grade 8th in a Private International School. The quantitative data of this research was obtained through objective test, while the qualitative data was gained through rubric and questionnaire. Students' creativity is measured by Creative Product Analysis Matrix (CPAM). On the other hand, students' conceptual understanding is measured based on Bloom's taxonomy cognitive level through objective test and being analyzed by using SPSS 18.0. In this research, both classes received conventional instruction. The experiment class' instruction was supplemented with the card game, while the control class' instruction was reinforced with group presentation and the making of question-answer poster. The results show that the students who learn excretory system through educational card game as intervention are more creative and have better conceptual understanding than another class which uses question-answer poster. That occurs because educational card game is a method that can increase students' interest in learning activity, enhance learning motivation, and also learning effectiveness. Thus, it indicates that the implementation of educational card game in learning excretory system can improve students' creativity and students' conceptual understanding in secondary level. Key words: Educational card game, students' creativity, students' conceptual understanding, excretory system.